Bob the Builder. Bob's favorite adventures - Cockle, Jackie; Herbert, Nick.; Whitaker, Liz.; Morrissey, Neil.; Rackstraw, Rob.; Harbour, Kate.; McFarlane, Colin; Gideon, Llewella, 1967-; Jones, Sam.; Couvela, Paul.; Biddulph, Barbara; Markiewicz, Zyggy; et al. (Allen, TX : Hit Entertainment, 2004)
Ballroom Bob: Bob doesn't have time to practice his new dance steps because he's been so busy building the dance floor for the town dance. Bob's Auntie: When Bob mistakenly thinks his Aunt Dora is coming for a visit, he and his crew frantically work to get the yard spick-and-span. Bob's pizza: While Bob and Spud help Mr. Sabatini deliver pizzas, Spud helps Wendy by stopping traffic while she works on the road. Forget me know Bob: When Bob's new personal organizer fails to work, he quickly becomes disorganized.
Ballroom Bob / Simon Jowett -- Bob's Auntie / Jimmy Hibbert -- Bob's pizza / Ian Carney -- Forget-me-knot Bob / Ben Randall.
Director of photography, Sam Jones ; supervising animator, Paul Couvela ; art directors, Barbara Biddulph, Samantha Hanks, Lucille Klassen-Bos ; editor, Zyggy Markiewicz, Adam Taylor, Bruce Marshall ; music, Paul K. Joyce ; costume designer, Karen Betty, Geraldine Corrigan.
Voices: Neil Morrissey, Rob Rackstraw, Kate Harbour, Colin McFarlane, Llewella Gideon.
MPAA rating: Not rated.
DVD, Region 1, full screen (1.33:1) presentation; Dolby Digital.
Closed-captioned.
Keywords: Bob the Builder (Fictitious character) -- Juvenile drama; Construction workers -- Juvenile drama; Construction equipment -- Juvenile drama; Animated television programs; Children's television programs; Films for the hearing impaired